Performance Effectiveness Of Mediators In Settlement Of Industrial Relations Disputes In Manpower And Transmigration Services - Sarah Magfirah Daud (Universitas Negeri Gorontalo, 2020)
The purpose of this study is to describe and identify the performance of mediators in resolving industrial relations disputes at the Manpower and Transmigration Office of Gorontalo Regency and to identify and analyze the inhibiting factors experienced by mediators in resolving industrial relations disputes if they fail. The research method used is sociological juridical, namely examining applicable legal provisions and what happens in society or research conducted on real conditions that occur in society. The results of this study are that the success of a mediation process depends on the performance of the mediator himself in the settlement of industrial relations disputes. According to the mediator at the Manpower and Transmigration Office of Gorontalo Regency, cases that are often handled and resolved at the mediation stage are cases of disputes over the termination of employment (PHK). In the mediation process, failure is something that is also found in reaching a collective agreement, because several internal and external factors make the mediation process unsuccessful, so it is recommended to go to court. The conclusion from the research is that the performance of the mediator in the settlement of industrial relations disputes at the Department of Manpower and Transmigration of Gorontalo Regency has been running according to the applicable regulations and has not been effective.